Efeito das temperaturas de têmpera e de revenido na resistência à corrosão da camada martensítica de alto nitrogênio produzida por SHTPN sobre o aço AISI 409 - Berton, Elisiane Maria (2014)
Due to high corrosion resistance, stainless steels have a wide applicability in many industrial sectors, such as, chemical, petrochemical and food industries. With the demand for corrosion resistance materials becoming more stringent, methods that improve the relation corrosion resistance and mechanical properties of these steels has been studied by many researchers. In order to increase the mechanical strength, surface hardness and corrosion resistance of stainless steels we proposed the introduction of nitrogen in solid solution by the process of SHTPN (Solution Heat Treatment after Plasma Nitriding), under development in GrMaTS/UTFPR . Nitrogen in solid solution has some advantages over materials that have only carbon in the structure such lower tendency for precipitation and stabilization of the passive layer. In addition, the nitrogen reacts in the anodic area, which neutralizes the effect in the acidity thus improving the corrosion resistance. This research evaluate the corrosion resistance of ferritic stainless steel AISI 409, after obtaining a martensitic layer enriched with nitrogen, in solid solution, by SHTPN process. Effects of tempering temperature (200, 400 and 600 °C) and austenitization temperature (950 to 1050 °C) in the microstructure, hardness and corrosion resistance of martensitic layer obtained. Corrosion resistance was evaluated by cyclic polarization technique, with a NaCl solution 0.5 mol/L, and hardness profiles obtained by measuring the Vickers hardness with a load of 0.05 kgf (0.49 N). Samples microstructure was investigated by optical microscopy, scanning electron microscopy and X- ray diffraction. Results indicate that the treatment of SHTPN promoted the formation of a martensitic nitrogen layer, with consequent increase of hardness of 160 HV to 580 HV on sample surface. Tempering treatments, realized after SHTPN did not significantly affect the hardness of steel, however, has refined and improved the distribution of nitrogen martensite. Corrosion results of sample treated and annealed at 200 °C indicate higher or equal resistance to that of the untreated ferrite materials (AISI 409) corrosion. Samples that were annealed at temperatures of 400 and 600 °C showed a decrease in the corrosion resistance as well as a decrease in hardness was observed in the sample tempered at 600 °C.